A modal displacement-based design method for irregular building frames equipped with elastomeric bearings. (July 2022) - Mohammadian Shalmaee, Mahdi; Pourzeynali, Saeid
Abstract: In this study, a Modal Displacement-Based Design (MDBD) method for seismic design of base isolated building frames with vertical irregularity has been proposed using principles of the Direct Displacement Based Design method and evaluated through the Nonlinear Time History Analysis (NTHA). The structural models used here are regular and irregular building frames equipped with elastomeric bearings. By comparing the results of the proposed MDBD method with those of the NTHA, it can be concluded that the proposed procedure is able to predict seismic demands of this kind of structures with acceptable accuracy. The advantage of this method is not only that it can predict the design values in a way that the maximum seismic responses of structure reach to the pre-selected values, but also can predict the true displacement profile of frame and find where maximum drifts happen.